2002
DOI: 10.1128/aac.46.8.2490-2497.2002
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Based Identification and Classification of Antibacterial Agents: Second-Generation Escherichia coli Reporter Strains and Optimization of Detection

Abstract: Escherichia coli strains bearing single-copy fusions between the lacZ reporter gene and the cspA, ibp, or P3rpoH stress promoters offer a simple means to detect sublethal concentrations of antibacterial agents interfering with prokaryotic translation or cell envelope integrity while simultaneously providing information on the mechanism of action of the test compound (A. A. Bianchi and F. Baneyx, Appl. Environ. Microbiol. 65:5023-5027, 1999). Here, we expand the usefulness of this system by (i) demonstrating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 39 publications
1
47
0
2
Order By: Relevance
“…These results agree with our observation that the expression of G. stearothermophilus V genes protects E. coli against the toxic effects of hydrogen peroxide and diamide. This protective effect was further observed in transformed E. coli reporter strains ADA110 and ADA310 (30), which exhibited important reductions of ␤-galactosidase activity when exposed to K 2 TeO 3 . The levels of ␤-galactosidase in these E. coli ADA strains expressing Geobacillus genes were indistinguishable from those of controls grown in the absence of tellurite (Fig.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…These results agree with our observation that the expression of G. stearothermophilus V genes protects E. coli against the toxic effects of hydrogen peroxide and diamide. This protective effect was further observed in transformed E. coli reporter strains ADA110 and ADA310 (30), which exhibited important reductions of ␤-galactosidase activity when exposed to K 2 TeO 3 . The levels of ␤-galactosidase in these E. coli ADA strains expressing Geobacillus genes were indistinguishable from those of controls grown in the absence of tellurite (Fig.…”
Section: Resultsmentioning
confidence: 71%
“…E. coli ADA strains induce the expression of the ␤-galactosidase gene when exposed to different stress conditions (30). These strains carry single-copy fusion genes consisting of the lacZ reporter gene fused to the promoter regions of the highly inducible cytoplasmic small heat shock proteins IbpA and IbpB (ADA110), the major cold shock protein CspA (ADA310), the P3 promoter of the rpoH gene (activated upon periplasmic protein misfolding) (ADA410), or the SOS-inducible sulA promoter (ADA510) (30).…”
Section: Resultsmentioning
confidence: 99%
“…Activation of oxidative stress-inducible promoters by potassium tellurite supports this assumption. Recent results from our laboratory have shown that tellurite-mediated induction of the ibpA gene promoter, a gene related with oxidative response (39,40), is blocked by yqhD overexpression. Similar findings were not observed with other stress-responsive promoters not related to oxidative stress as cspA, p3RpoH, and sulA.…”
Section: Figure 3 Oxidized Proteins In E Coli a Sds-page Showing mentioning
confidence: 98%
“…Because of their sensitivity to SOS system-inducing conditions (24), lon mutants usually present an increased sensitivity to quinolones (23,38). The spontaneous lon1::IS186 mutant AB1899 has been reported to present increased resistance to multiple antibiotics compared to its parental strain, AB1157 (Table 3) (32).…”
Section: Vol 188 2006 New Mutations Conferring a Mar Phenotype 4417mentioning
confidence: 99%